FORMULATION AND EVALUATION OF ACARBOSE PELLETS BY EXTRUSION SPHERONIZATION TECHNIQUE - M. R., DILIP; RUBY, J. JOYSA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of our work is to formulate and evaluate acarbose pellets for sustain drug delivery. The present study was aimed to develop sustain drug delivery system of acarbose pellets by extrusion spheronization technique using different polymers like Hydroxypropyl methyl cellulose, chitosan, ethylcellulose, microcrystalline cellulose. Pelletization of acarbose was done to achieve sustain drug release profile suitable for oral administration. Methods: The acarbose pellets were prepared by extrusion spheronization technique. The Fourier transform-infrared spectrum (FT-IR) and Differential scanning calorimetry thermogram of pure drug and drug-polymer blend showed the stable character of acarbose in the pellets. The prepared pellets were evaluated for different quality control parameters like particle size analysis, drug content, and Drug release characteristics. Results: The results obtained from different quality control parameters are within acceptable range and In vitro dissolution studies indicated that drug release from pellets follows zero-order kinetics with sustain release drug release up to 12 h with the use of ethyl cellulose as a sustain release polymer and mechanism of drug release is non-fickian. The formulated pellets were stable with respect to their physicochemical characters and drug content over a period of 60 d at accelerated stability condition. Conclusion: From present study, it was concluded that formulation of acarbose pellets by this will be a promising technique for the preparation of pellets to sustain drug release for the treatment of diabetes with better patient compliance.